Catechin hydrate as an eco-friendly biocorrosion inhibitor for 304L stainless steel with dual-action antibacterial properties against Pseudomonas aeruginosa biofilm. (15th August 2019) - Lekbach, Yassir; Dong, Yuqiao; Li, Zhong; Xu, Dake; El Abed, Soumya; Yi, Yang; Li, Linwei; Ibnsouda Koraichi, Saad; Sun, Tiemin; Wang, Fuhui
Graphical abstract: Highlights: Catechin hydrate inhibits the formation of P. aeruginosa biofilm and kills the mature biofilms. Catechin hydrate downregulates the expressions of genes responsible for quorum sensing and biofilm formation. Catechin hydrate inhibits the corrosion caused by P. aeruginosa by adsorbing on the 304L stainless steel coupon surfaces. The cytotoxicity assay shows that catechin hydrate is an eco-friendly compound. Abstract: Catechin hydrate (CH) was evaluated for its antimicrobial, antibiofilm and anticorrosion activities for 304L stainless steel against Pseudomonas aeruginosa by means of surface analysis, electrochemical measurements and quantum chemical calculations. Results showed that CH inhibited the P. aeruginosa biofilm formation and killed mature biofilms. Electrochemical data demonstrated that CH inhibited the corrosion induced by P. aeruginosa with an excellent inhibition efficiency of 99.8%. It was also found that CH significantly downregulated the expressions of critical genes for quorum sensing and biofilm formation as revealed by qPCR data. In vitro cytotoxicity assay showed that CH was non-toxic to MC3T3-E1 cells.